Legal Protection Of Property Rights In The Natural Dyes Of Sikka Woven Fabrics Industry Assessed From Law Number 28 Year 2014 In Terms Of Copyright - Theresia Emilia Beci da Cunha (Universitas Widya Gama Malang, 2020)
This study aims to study and analyze the principles in the Copyright Law and the qualifications of the Sikka Weaving natural coloring compound in Article 40 of Law Number 28 Year 2014 regarding Copyright as Intellectual Property Rights. The method used in this research is normative legal research method. Normative legal research examines library materials or secondary materials by collaborating the statute approach and the descriptive conceptual approach. The results of the findings and analysis of the study researchers, Intellectual Property Rights in the form of natural dye material for hand woven fabrics in Sikka Regency are protected by Law No. 28/2014. The Central Government provides access and facilities in the context of IPR. The role of the Regional Government of Sikka Regency is the main element in maintaining traditional knowledge. The role of the government is in the form of making regional regulations (PERDA) on IPR for Sikka's natural dye weaving. PERDA which refers to the knowledge of the local community, the use and preservation of natural dyes by the community in the process of making Sikka tie weaving. This study recommends that the Sikka Regency should make regional rules about the natural coloring weaving Sikka Regency.